'I am happy to start the conversation': Examining sport media framing of Jason Collins' coming out and playing in the NBA. (September 2015) - Kian, Edward M; Anderson, Eric; Shipka, Danny
A textual analysis examined US media framing of National Basketball Association (NBA) player Jason Collins' coming out as the first 'active' gay athlete in one of the four most popular US professional men's team sport leagues. We analyzed all articles on Collins published over a four-day period in the five most circulated US newspapers and five most trafficked USA-based sport websites after he came out publicly, and then analyzed those same publications over a three-day period following his signing with and playing for the Brooklyn Nets as an openly gay player. Journalists framed Collins' self-outing as a landmark for US sport, noting that both sport and the USA are now far more accepting of sexual minorities. The few media members and athletes who criticized Collins or homosexuality were framed as antiquated outliers. Sports journalists continued to frame Collins as a hero after he signed with the Brooklyn Nets. Upon his return to the NBA nearly 10 months after coming out, prominent African-American basketball players and Collins' teammates with Brooklyn were quoted as equating homophobia with racism in offering their support for Collins. Overall, media framed sport as an inclusive, accepting institution for gays, countering most previous research on homosexuality in sport media.